2011
DOI: 10.1016/j.schres.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal movements are associated with poor psychosocial functioning in adolescents at high risk for psychosis

Abstract: The period immediately preceding the onset of overt psychosis is characterized by a range of symptoms and behaviors including emerging attenuated psychosis, spontaneous movement abnormalities, and a broad decline in role and social functioning. Recent evidence suggests that basal ganglia dysfunction, which is implicated in the development of psychotic symptomatology, may manifest in the form of both movement abnormalities and deficits in processes integral to psychosocial functioning. However, little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…In the frontal cortex, CHR exhibit both structural alterations (e.g., gray matter, cortical surface, integrity)(Bloemen et al, 2010; Fusar-Poli et al, 2011a; Iwashiro et al, 2012; Jung et al, 2012; Kambeitz-Ilankovic et al, 2015; Mechelli et al, 2011; Nenadic et al, 2015; Pantelis et al, 2009) (reviewed in (Brent et al, 2013; Smieskova et al, 2013) and functional changes in response to WM and other cognitive tasks (Allen et al, 2011; Dutt et al, 2015; Fusar-Poli et al, 2011b; Natsubori et al, 2014). In the PHP and medial temporal lobe (MTL, including the hippocampus, amygdala and surrounding entorhinal and perirhinal cortices), CHR most reliably demonstrate structural alterations (e.g., reduced gray matter, cortical thinning)(Buehlmann et al, 2010; Jung et al, 2011; Mechelli et al, 2011; Mittal et al, 2011; Pantelis et al, 2003; Tognin et al, 2013), with one previous study demonstrating task-induced functional alterations in antipsychotic naïve CHR (Allen et al, 2011). In the striatum, altered striatal activity, as well as altered striatal dopamine (Allen et al, 2012; Fusar-Poli et al, 2011e), glutamate (de la Fuente-Sandoval et al, 2011), GABA (Kang et al, 2014) and 5HT(2A) binding (Hurlemann et al, 2008), have been reported in CHR.…”
Section: Discussionmentioning
confidence: 85%
“…In the frontal cortex, CHR exhibit both structural alterations (e.g., gray matter, cortical surface, integrity)(Bloemen et al, 2010; Fusar-Poli et al, 2011a; Iwashiro et al, 2012; Jung et al, 2012; Kambeitz-Ilankovic et al, 2015; Mechelli et al, 2011; Nenadic et al, 2015; Pantelis et al, 2009) (reviewed in (Brent et al, 2013; Smieskova et al, 2013) and functional changes in response to WM and other cognitive tasks (Allen et al, 2011; Dutt et al, 2015; Fusar-Poli et al, 2011b; Natsubori et al, 2014). In the PHP and medial temporal lobe (MTL, including the hippocampus, amygdala and surrounding entorhinal and perirhinal cortices), CHR most reliably demonstrate structural alterations (e.g., reduced gray matter, cortical thinning)(Buehlmann et al, 2010; Jung et al, 2011; Mechelli et al, 2011; Mittal et al, 2011; Pantelis et al, 2003; Tognin et al, 2013), with one previous study demonstrating task-induced functional alterations in antipsychotic naïve CHR (Allen et al, 2011). In the striatum, altered striatal activity, as well as altered striatal dopamine (Allen et al, 2012; Fusar-Poli et al, 2011e), glutamate (de la Fuente-Sandoval et al, 2011), GABA (Kang et al, 2014) and 5HT(2A) binding (Hurlemann et al, 2008), have been reported in CHR.…”
Section: Discussionmentioning
confidence: 85%
“…Second, evidence has been gathering over the past two decades to suggest that spontaneous motor abnormalities can occur as a function of pathophysiology in a sizeable subsample of individuals with schizophrenia. 15,16 This has been demonstrated in studies of unaffected relatives, 17 prodromal youth, 18,19 as well as medication naïve groups (for a review see Pappa and Dazzan 20 ). Although it is still difficult to study motor behaviors in patients treated with any medications that affect subcortical dopamine (DA) activity, a more widespread understanding that these behaviors reflect pathogenic processes, research approaches with low dosage inclusion criteria and medication-free or medication-naïve patients, as well as designs focusing on individuals who represent a lower vulnerability loading on the psychosis continuum (ie, populations with elevated schizotypy, schizotypal personality disorder, and nonclinical psychosis exhibit motor abnormalities but are often unmedicated), [21][22][23][24][25][26] will continue to open new avenues.…”
Section: At Issuementioning
confidence: 87%
“…Unfortunately, the cross-sectional design of our study does not allow us to conclude for the fourth criterion “state independent in affected individuals,” (i.e., manifests in an individual whether or not illness is active). But, several studies suggest that adolescents who later develop schizophrenia exhibit motor behavior disorders, particularly motor dyscoordination, well before overt manifestations of the illness (Leask et al, 2002; Mittal et al, 2011). Future research should assess the presence of IMC impairment in adolescents with a high risk of schizophrenia in order to confirm the fourth criterion.…”
Section: Discussionmentioning
confidence: 99%
“…NSS are observable in first-episode patients (Bachmann et al, 2005), and even prior to antipsychotic administration (Scheffer, 2004; Chen et al, 2005). Additionally, adolescents who later develop schizophrenia exhibit signs of neurological abnormalities, particularly motor dyscoordination, well before overt manifestations of the illness (Leask et al, 2002; Mittal et al, 2011), providing further evidence for a fundamental role of motor dysfunctions as an early constitutional vulnerability of schizophrenia. Several studies showed that NSS are present in relatives of schizophrenia patients (Chan et al, 2010; Neelam et al, 2011), and are among the most promising of the candidate intermediate phenotypes (Chan and Gottesman, 2008).…”
Section: Introductionmentioning
confidence: 99%